Generation of a heterozygous Calsequestrin 2 F189L iPSC line (UMGi158-B) by CRISPR/Cas9 genome editing to investigate the cardiac pathophysiology of Takotsubo Syndrome and Catecholaminergic Polymorphic Ventricular Tachycardia - Gideon Syed Ali; Sabine Rebs; Hanna Eberl; Clarissa Zinke; Daniela Hübscher; Wiebke Maurer; Alexandra Busley; Lukas Cyganek; Katrin Streckfuss-Bömeke (Stem Cell Research)
Takotsubo Syndrome (TTS) is a potentially life-threatening disease characterized by a transient left ventricular apical akinesia in response to β-adrenergic overstimulation. Since a genetic predisposition is assumed, we generated an iPSC-line carrying a p.F189L mutation in the calcium buffering protein Calsequestrin 2 (CasQ2). This missense mutation was previously discovered in a TTS patient and further described in a family with Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT). The established cell line is used to investigate the main mechanisms leading to TTS and CPVT using a patient-specific stem cell approach.